Alterações em características físicas de solos cultivados com pastagem - Gusmão Dadalto, Gilmar; Marciano da Costa, Liovando; Moura Filho, Waldemar (Revista Ceres, 2025)
The main purpose of this research was to find out the possible changes of some physical characteristics of three soils under pasture: Red Yellow Eutrophic Podzolic Soil (PeTa), two years under cultivated pasture; Cambisol Latosol Eu- trophic Soil (CeL) under cultivated pasture for five years and Red Yellow Latosol medium texture-Quartzy-Sand (LVm/AQ) also under cultivated pasture for two pe- riods of time, five and nine years. The above three soil classes under natural vege- tation were also sampled as a reference basis. Results showed that pasture cultivation in PeTa tended to improve soil strue- ture as evaluated by bulk density, pore space distribution and aggregate analyses. Increments in bulk density and in porous spaces on the superficial layer of CeL cultivated with pasture demonstrate the degradational effect of cattle grazing over the soil. Cultivation of pasture increased bulk density as well as LVm/AQ disaggrega- tion, reducing its total porosity and macroporosity.